Early Stage Versus Late Stage Periarticular Injection during Unicompartmental Knee Arthroplasty for Postoperative Pain Relief: A Randomized Controlled Trial - Chen, Wang; Sun, Jian-Ning; Hu, Zheng-Hao; Zhang, Yu; Chen, Xiang-Yang; Feng, Shuo (The Journal of Knee Surgery, 2021)
Controlling postoperative pain after unicompartmental knee arthroplasty (UKA) is essential to improve patient satisfaction and promote early recovery. The purpose of this study was to investigate the difference in clinical efficacy between early and late stage periarticular injection during UKA for postoperative pain relief. Eighty-four patients meeting the inclusion and exclusion criteria were randomly divided into the early stage periarticular injection group and late stage periarticular injection group by using a random number tables method. The difference between the two groups was that the early stage periarticular injection group received superficial injection before the joint incision, while the late stage periarticular injection group received superficial injection after implantation of the prosthesis. Deep injection and other perioperative conditions of the two groups were controlled identically. The primary outcome of the study was the recovery room immediate visual analog scale (VAS) at rest. The secondary outcomes were the postoperative VAS (at rest) at 3, 6, 9, 12, 18, 24, 48, 72, 96, and 120 hours, drug dosage of rescue analgesia, range of motion (ROM), and complications. The recovery room immediate VAS (at rest) in the early stage periarticular injection group was significantly lower than that of the late stage periarticular injection group (21 ± 24 vs. 32 ± 34 mm, p = 0.018), the average difference of the VAS reached the minimal clinically important difference. No statistically significant difference in postoperative drug dosage of rescue analgesia, ROM, and complications. Preemptive analgesia combined with the early stage periarticular injection can better alleviate postoperative pain than the late stage periarticular injection.
Keywords: unicompartmental knee arthroplasty; periarticular injection; preemptive analgesia; pain; randomized controlled trial